The impact of exercise on mental health during the COVID-19 pandemic: a systematic review and meta-analysis - Wang, Chaochao; Tian, Zuguo; Luo, Qiaoyou (Frontiers in Public Health, 2023)
Amidst the COVID-19 pandemic, there has been a global surge in mental health challenges. This study (PROSPERO CRD42023443860) aimed to investigate the impact of exercise on individuals' mental health through systematic evaluation and meta-analysis to develop a scientific exercise program. A comprehensive search of PubMed, Web of Science, and SCOPUS up to August 2023 yielded 12 eligible studies out of 10,343 initially identified records for systematic evaluation and meta-analysis. The Cochrane Risk Assessment Tool gauged the methodological quality of the included literature. Exercise significantly improved anxiety (SMD -0.81, 95% CI -1.10 to -0.52, p < 0.00001), depression (-1.02, 95% CI -1.42 to -0.62, p = 0.0001), stress (-1.05, 95% CI -1.33 to -0.78, p < 0.00001), and quality of life (1.11, 95% CI 0.81 to 1.41, p < 0.00001). Subgroup analyses indicated that a single exercise session lasting 30-40 minutes had the most pronounced effect on reducing anxiety (-1.29, 95% CI -1.12 to -0.86, p < 0.00001) and depression (-1.76, 95% CI -2.24 to -1.28, p < 0.00001). Similarly, an exercise frequency of 3-5 times per week yielded the greatest benefits for anxiety (-1.31, 95% CI -2.15 to -0.46, p < 0.00001) and depression (-1.27, 95% CI -2.11 to -0.41, p = 0.0003). Notably, exercise exhibited its most significant impact on depression improvement in the 40-64 age group (-1.32, 95% CI -1.78 to -0.86, p < 0.00001). Moreover, exercise notably enhanced anxiety levels among individuals in middle and upper-income brackets (-0.99, 95% CI -1.11 to -0.87, p < 0.00001). Exercise alleviated anxiety disorders, depression, stress levels, and quality of life during the COVID-19 pandemic. The most significant impact on anxiety and depression improvement is achieved by engaging in 30-40 minutes of exercise sessions, 3-5 times per week.